Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Diversifying the structural architecture of synthetic oligomers: the hetero foldamer approach - Roy, Arup; Prabhakaran, Panchami; Baruah, Pranjal Kumar; Sanjayan, Gangadhar J. (Chemical Communications, 2011)
Conformationally ordered synthetic oligomers, also called ``foldamers'', have attracted considerable attention in recent years owing to their ability to mimic the structural architecture of biopolymers and also because of their potential applications in biomedical and material science fields. Until recently, the major focus in this area has been the development of oligomers featuring a single type of monomer building blocks. However, due to the enormous possibility of augmenting the conformational space available for oligomer design, the hetero foldamer approach has been introduced very recently. This feature article aims to describe foldamers with unique structural architectures, exclusively featuring heterogeneous backbones (hetero foldamers).

Sugar-amino acid cyclic conjugates as novel conformationally constrained hydroxyethylamine transition-state isosteres - Roy, Arup; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2012)
Hydroxyethylamine (HEA) isosteres have previously been shown to display a multitude of biomedical applications. In fact, the first protease inhibitor, saquinavir is an HEA based peptidomimetic. Herein we describe an easy-to-operate synthetic route to a series of carbohydrate-based conformationally constrained hydroxyethylamine (HEA) isosteres featuring amino acid side chains, starting from D-glucose. This class of novel sugar-amino acid-tethered conformationally restricted HEA systems may have bearing in practical application, particularly in the development of conformationally restricted protease inhibitors. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Conformationally constrained; D-Glucose; hydroxyethylamine isosteres; protease inhibitor; Reductive amination

Heterogeneous foldamers from aliphatic-aromatic amino acid building blocks: current trends and future prospects - Nair, Roshna V.; Vijayadas, Kuruppanthara N.; Roy, Arup; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2014)
Chemists' constant pursuit of understanding of the underlying principles of nature's most intricate phenomenon such as protein folding has led to the development of the field of foldamers. The emergence of diverse classes of unnatural amino acid building blocks has unleashed countless opportunities to design, develop and explore the structural and functional aspects of synthetic peptides. One current trend in foldamer chemistry is the heterofoldamer approach, which involves systematic stoichiometric variation of various natural/unnatural amino acid residues, leading to conformational ordering with intriguing structural architectures. In this regard, the incorporation of aromatic amino acids provides efficient structural rigidification and tunability to the molecular scaffolds, which can exhibit a range of secondary structural features. Recent times have witnessed an upsurge of foldamers featuring aliphatic-aromatic residues with diverse structural propensities. This review is an effort to cover this rapidly developing field of foldamer science and also to envisage its future perspectives.
Keywords: Amino acids; Conformation analysis; Foldamers; hydrogen bonding; Peptides; Stacking interactions

Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Ligand-promoted intramolecular dehydrogenative cross-coupling using a Cu catalyst: direct access to polycyclic heteroarenes - Ray, Devalina; Manikandan, T.; Roy, Arup; Tripathi, Krishna N.; Singh, Ravi P. (Chemical Communications, 2015)
A copper(II)-promoted intramolecular C-H coupling reaction between indole-2 and imidazole-2 moieties has been developed for polycyclic heteroarene synthesis. The method provides direct access to biheteroaryl incorporated polycyclic frameworks, which are of huge interest in the area of functional materials and drug-discovery.